Some Aspects of Canadian Urbanization from 1850 to 1921 - Goheen, Peter (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1980)
The urbanization of Canada is measured from several perspectives: the growth of urban population from 18 per cent of the total in 1871 to 47 per cent by 1921; the policies of private and government agencies, which stimulated industrialization in central Canada and tied the West and the Atlantic regions to central Canada through a transcontinental railway system; and the rise of large cities such as Montreal and Toronto, which dominated the emerging national system, which in turn was subject to international influences.